1985
DOI: 10.1111/j.1751-1097.1985.tb03520.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOPHYSICS IN LIQUID CRYSTALS. FLUORESCENCE BEHAVIOR OF CHLOROPHYLL‐a IN DODECYLCYANOBIPHENYL

Abstract: Fluorescence behaviour of chlorophyll-a in a liquid crystalline medium, dodecyl cyanobiphenyl, has been investigated as a function of temperature and concentration. At concentrations of 6 x lo-'' M , emission in the Q-band region exhibited peaks in the crystal at 650,695 and 735 nm as well as the monomer band at 675 nm. Dilution studies indicate that these additional bands probably arise from aggregation of the chlorophyll.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As a result of the interaction of liquid crystal with the orienting layer the liquid crystal molecules are oriented [1][2][3]. Due to the guest-host effect also the dye molecules are uniaxially oriented along the axis located in the plane of the electrodes [1][2][3], in such a system, as it was shown previously, the degree of orientation of stilbazolium merocyanines is high [4]. Figure 1 shows the chemical formulae of stilbazolium merocyanines used…”
Section: Introductionmentioning
confidence: 67%
“…As a result of the interaction of liquid crystal with the orienting layer the liquid crystal molecules are oriented [1][2][3]. Due to the guest-host effect also the dye molecules are uniaxially oriented along the axis located in the plane of the electrodes [1][2][3], in such a system, as it was shown previously, the degree of orientation of stilbazolium merocyanines is high [4]. Figure 1 shows the chemical formulae of stilbazolium merocyanines used…”
Section: Introductionmentioning
confidence: 67%
“…The photophysics of Chl a that determines the absorption and emission of polarized light is particularly complicated in water-containing systems because of the formation of dimers and oligomers so that the nature of the actual photoresponsive unit is not always completely clear. Here we wish to tackle the problem of describing the order and rotational dynamics of Chl a in a possibly simpler model system: an oriented nematic liquid crystal. A number of studies have already been reported for Chl a dissolved in liquid crystals using transient EPR, , resonance Raman, and fluorescence techniques, particularly by the Polish school. In these studies a number of simplifications have been necessarily employed; in particular Chl a has been treated as a rigid uniaxial object in its static and dynamical behavior 20 or at least in its dynamics, assuming uniaxial symmetry of the rotational diffusion tensor. Moreover the temperature dependence of the order parameters has not really been determined.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Here we wish to tackle the problem of describing the order and rotational dynamics of Chl a in a possibly simpler model system: an oriented nematic liquid crystal. A number of studies have already been reported for Chl a dissolved in liquid crystals using transient EPR, 15,16 resonance Raman, 17 and fluorescence techniques, 18 particularly by the Polish school. [19][20][21] In these studies a number of simplifications have been necessarily employed; in particular Chl a has been treated as a rigid uniaxial object in its static and dynamical behavior 20 or at least in its dynamics, 16 assuming uniaxial symmetry of the rotational diffusion tensor.…”
Section: Introductionmentioning
confidence: 99%